An Acquired Form of Dandy-Walker Malformation with Enveloping Hemosiderin Deposits. (25th October 2017) - Shiohama, Tadashi; Ando, Ryo; Fujii, Katsunori; Mukai, Hiroki; Naruke, Yuki; Sugita, Katsuo; Kato, Eiji; Shimojo, Naoki
Abstract : Dandy-Walker malformation (DWM) is a posterior fossa anomaly characterized by hypoplasia and upward rotation of the cerebellar vermis and cystic dilation of the fourth ventricle. The cyst of DWM rarely extends posteriorly to almost completely fill the entire posterior fossa, which mimics primary cerebellar agenesis, a cerebellar porencephalic cyst, and an arachnoid cyst due to the lack of clarity of the thin cystic wall. A 10-month-old female born at 23 weeks' gestation with cerebellar hemorrhage in the neonatal period was admitted to our hospital with dysphagia and side-to-side head bobbing. The detection of hemosiderin deposits enveloping the cyst wall by T2 star-weighted angiography (SWAN) was useful for the differential diagnosis of an acquired form of DWM from primary cerebellar agenesis. Cyst fenestration successfully improved dysphagia and head bobbing. A pathological specimen of the perforated cyst consisted of collagen fibers with hemosiderin deposits but lacked congenital cyst components. In infants with posterior fossa cysts, SWAN will be useful for a differential diagnosis between DWM and primary cerebellar agenesis.